TAKWIL EPISTEMOLOGIS IBN SÎNÂ ATAS SURAH AL-NÛR AYAT 35 - Al-Walid, Kholid (ULUL ALBAB Jurnal Studi Islam, 2018)
Ibn Sînâ is known as a rational philosopher who is often confronted with theologians who consider his views contrary to the principles of religion (naṣṣ). This paper reveals that Mashâiyyah philosophy built by Ibn Sînâ still relies on Islam and even make the verses of the Qur'an as a construct of ideas. In this paper, the author also tries to reveal epistemological ta’wîl employed by Ibn Sînâ in interpreting verse 35 of surat al-Nûr, which is generally understood sufistically, but in his view it might be understood differently. This proves that Ibn Sînâ hold on to naṣṣ. What distinguishes him with most theologians or sufis is the understanding of naṣṣ. Although it is apparent that Ibn Sînâ's epistemological outlook seemed to justify the Unity of Subject-Object theory as later Mulla Ṣadrâ was proposed, there was a fundamental difference between the two. The epistemological ta’wîl is a new reading of the philosophical style in Qur’anic exegesis on the one hand, which is different from the rationalization of tafsîr or the epistemology of tafsîr in the other one.